2021
DOI: 10.1002/nme.6682
|View full text |Cite
|
Sign up to set email alerts
|

Submodeling in wear predictive finite element models with multipoint contacts

Abstract: The application of the submodeling technique to finite element (FE) wear analyses has been recently proposed as an efficient solution to reduce the computational cost of the simulations and provide accurate numerical results.However, the method was validated only on single point contact cases. The present study proposes a generalization of the wear submodeling procedure that can be used to speed up FE wear simulations with multipoint contacts. The modified global-local procedure is applied and evaluated on a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The initial contact pressure calculated analytically based on the Archard wear theory is 37 GPa. Thus, the validation parameters of the FE model of the wear test will be the contact pressures and worn volumes. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial contact pressure calculated analytically based on the Archard wear theory is 37 GPa. Thus, the validation parameters of the FE model of the wear test will be the contact pressures and worn volumes. , …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the validation parameters of the FE model of the wear test will be the contact pressures and worn volumes. 29,30 FE mesh generation was performed in Ansys Fluent 2022 R2 software. The 2D axisymmetric model of the wear test is fixed to the ground, and the indenter moves into the sample and along its surface according to the experimental conditions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Therefore, the sub-model method is suitable for wear analysis of large and complex structures. The program for the wear sub-model mainly consists of three steps [52], which are shown in Figure 5a. The first step is to determine the boundary conditions required for creating a detailed local model based on the initial rough FE global model.…”
Section: Sub-modelmentioning
confidence: 99%
“…Eventually, the local model, to which boundary conditions from the global model are applied, is used to conduct the wear simulation. The research of Curreli et al [52,53] on the substructure method showed that the sub-model method can greatly reduce the computational cost of FE wear simulation. In particular, in the biomedical field, complex finite element models result in high time costs [26].…”
Section: Sub-modelmentioning
confidence: 99%
See 1 more Smart Citation